Guyana, fragile frontier : loggers, miners and forest peoples - Colchester, Marcus (London : Latin America Bureau, 1997)
From trading allies to colonial subjects, 5. -- Plantation politics, 25. -- Development domination, 36. -- Roads and ranches, 45. -- Undermining the interior, 61. -- Forets for sale, 96. -- Ameridian survival, 127. -- Future options, 141
Bibliografía p. 159-66